アラスカ ポイントバロー ノ チャクショク カイヒョウ カラ エタ ケイソウルイ ヨホウ - 福島, 博; フクシマ, ヒロシ; FUKUSHIMA, Hiroshi (国立極地研究所, 1965)
P(論文) Upon the request by Dr. H. MEGURO and others, the writer investigated the algae obtained by melting brown-colored sea ice collected at Point Barrow in Alaska in August 1964. The following is the result of investigation on part of the above material. Taxonomic study of the diatoms in the Arctic colored sea ice was made by CLEVE & GRUNOW (1880), CLEVE (1883), GRUNOW (1884), OESTERUP (1895), GRAN (1900), etc., and the diatoms in the Antarctic colored ice were studied by FUKUSHIMA (1961) and MEGURO (1961). The writer recognized about 40 kinds of diatoms in the material investigated this time. Among the above, 15 were not identified. Most of the identified diatoms and dominant species were endemic species of the Arctic Ocean. The writer cannot give a definite conclusion here becouse he investigated only one material, but the flora of the Antarctic colored ice seems to be largely different from that of the Arctic colored ice. The common point is that in either case, it is regarded as diatoms and also as dominant species, but, in the case of the Antarctic, cosmopolitan species were relatively abundant in association with endemic species of the Antarctic, and dominant species was sometimes also the endemic species of the Antarctic, sometimes cosmopolitan species in the case of the materials from the Arctic Ocean, most were endemic species of the Arctic and dominant species was also endemic species of the Arctic. departmental bulletin paper